Disney Movies as a Tool in Increasing Listening Skill - Natasha Maria Jeannie Manurip; Caroline Victorine Katemba (Departement of Mathematics Education, 2023)
This research was conducted to find out whether the use of Disney movies can help EFL college students to increase their listening skill and their perception toward the Disney movie. There are four research questions that are the purpose of this research: 1. What does EFL college students’ perception about the use of Disney movies as a tool in increasing their listening skill? 2. Does learning through feature movies (Disney) considered effective for EFL Students? 3. What are the benefits of using Disney movies as a tool in increasing listening skill? 4. What are the disadvantages of using Disney movies as a tool in increasing listening skill? This was quantitative research. The data was collected through an online questionnaire that was given to EFL college students from public and private universities in Indonesia. A total of 77 respondents participated in this study. The findings of this research showed that EFL college students that used Disney movies as their learning media had increased their listening skill and gained confidence and motivation in learning the English language.